Implementasi Program Baznas Microfinance Desa Badan Amil Zakat Nasional Di Kabupaten Maros (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to analyze and describe organizational and inter-organizational behavior, lower-level bureaucratic behavior and the behavior of target groups in the implementation of the National  Microfinance Baznas Program, National Zakat Agency in Maros Regency. This study was conducted in Maros Regency using qualitative descriptive research methods. Data collection were observation, interviews and documentation. Data validation was carried out through triangulation of sources, techniques and time. Data  analysis used  data reduction, data presentation and  conclusions. The results showed that the implementation process included organizational behavior and inter-organizational dimensions, namely commitment and coordination. The level of commitment of related agencies was quite high, while coordination of related agencies needed to be improved. The dimensions of lower-level bureaucratic behavior were organizational control and official professionalism. Organizational control was running well and the level of professionalism of the apparatus was quite high. The response  of the Village Microfinance Baznas was very supportive of this program because it was very helpful in terms of financing business capital.Keywords: Program Implementation,  Village Microfinance Baznas